Technology in EFL Teaching and Learning in Thailand: An Overview of Research and Issues - Deerajviset, Poranee (Journal of Mekong Societies, 2014)
Information and Communication Technology (ICT) has become the key issue and has a significant influence on current education (Welch, 2011). As for many other countries, technology has played an important role in education especially in language teaching and learning in Thailand. The application of technology in English as a Foreign Language (EFL) education is also a widely researched subject in Thailand. The aim of this article is to provide a review of current research on technology in EFL education in Thailand. The review aims to examine the effectiveness of technology for improving EFL teaching and learning, in relation to the language skills and areas. It also explores the limitations of current research on technology in EFL education in Thailand and provides implications for future research. Such knowledge will hopefully guide further development in research on technology in EFL teaching and learning in Thailand.